2017
DOI: 10.3389/fphar.2017.00809
|View full text |Cite
|
Sign up to set email alerts
|

α7 Nicotinic Agonist AR-R17779 Protects Mice against 2,4,6-Trinitrobenzene Sulfonic Acid-Induced Colitis in a Spleen-Dependent Way

Abstract: The existence of a cholinergic anti-inflammatory pathway negatively modulating the inflammatory and immune responses in various clinical conditions and experimental models has long been postulated. In particular, the protective involvement of the vagus nerve and of nicotinic Ach receptors (nAChRs) has been proposed in intestinal inflammation and repeatedly investigated in DSS- and TNBS-induced colitis. However, the role of α7 nAChRs stimulation is still controversial and the potential contribution of α4β2 nACh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Several studies have indicated that activating α7nAChR can alleviate colonic inflammation to a certain degree ( 18 , 19 ). The present study demonstrated that macrophage-specific expression of α7nAChR was induced in inflamed colons of DSS-induced colitis in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that activating α7nAChR can alleviate colonic inflammation to a certain degree ( 18 , 19 ). The present study demonstrated that macrophage-specific expression of α7nAChR was induced in inflamed colons of DSS-induced colitis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…This work demonstrates that α7nAChR serves a crucial role in the regulation of macrophage activation and is suggestive of a potential role for macrophage α7nAChR in inflammatory diseases such as colitis. Indeed, some studies suggest that α7nAChR plays a negative role in the progression of colitis ( 18 , 19 ). However, treatment with pharmacological agonists of α7nAChR in colitis induced intolerable side effects in an experimental mouse model, and large doses of such agonists may have disruptive effects on colon integrity and induce anxiety-like behavior ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immediately afterward, vessel disconnection around the spleen was performed with vessel clamp, No.0 operation silk thread, and scissors. Finally, we removed the spleen and sutured the abdominal musculature and skin [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Then, a stimulation at an intensity of 2 V (load voltage) and a frequency of 3 Hz was given for 15 minutes using the Electronic Acupuncture Treatment Instrument (96805- I Type, Xinsheng Industrial Limited Liability Company, Qingdao, China). For GTS21 (a specific agonist of α 7nAchR; ab120560, Abcam, England) administration, liquid medicine was injected to CLP rats intraperitoneally with a dose of 4 mg/kg/d for two days [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The length of colon and its weight were measured to assess deposition of fibrotic material and muscular contraction elicited by colitis induction; weight/length ratio was calculated to assess colon thickness, according to previously published criteria (Grandi et al, 2017).…”
Section: Methodsmentioning
confidence: 99%